Systems Transformation Science Group: Evaluation Report - Belbase, K.; Fabricius, C.; Howard, J.; Zake, J.; Corsetti, L.C.; Cekova, D. (2024)
The CGIAR 2030 Research and Innovation Strategy set the stage for ensuring that research provides solutions for development. The strategy was delivered through 33 initiatives grouped within three interlinked action areas: Systems Transformation (ST), Resilient Agri-food Systems, and Genetic Innovation. The ST Science Group (SG) contributes to food, land, and water across CGIAR’s five Impact Areas, supporting policy and decision-makers at multiple governance levels with timely policy-relevant insights.